The Effect of Marketing Mix on Purchase Decisions in Grilled Pempek Lenggang MSMEs at Pasar Lama, Tangerang City - Juliyano, Irvan; Nandang, Nandang; Rachmani, Nizza Nadya (TOFEDU: The Future of Education Journal, 2025)
The Pempek Panggang Lenggang MSME located in Pasar Lama, Kota Tangerang, has experienced a decline in turnover due to competition. This study to analyze the marketing profile and purchasing decisions as well as their influence. The study used a quantitative research method with a survey approach, and data was obtained through questionnaires administered to 100 respondents who had purchased Pempek Panggang Lenggang in the last three months. The analysis includes descriptive statistics, classical assumption tests, and hypothesis test. The results of the study indicates that the marketing mix has a positive influence on purchasing decisions. This study provides practical implications for SME practitioners in designing more effective marketing strategies and theoretical implications for the development of marketing literature in the SME culinary sector.